MEREKONSTRUKSI SISTEM PENDIDIKAN HINDU DALAM UPAYA MENUMBUH KEMBANGKAN BUDI PEKERTI PADA ANAK UNTUK MENJADI INSAN CERDAS DAN KOMPETITIF - Untung Suhardi (Sekolah Tinggi Agama Hindu Dharma Nusantara Jakarta, 2014)
This research used the qualitative approach which discusses about the re-understanding of the education system in an attempt to growing the Hindu manners in children. The research of Hindu educational system, such as the gurukula, asrhama, mandala is used by teachers in the past both in India up to the Majapahit era is widely used by later such as education; boarding school, pasraman and even the national education. This situation became unclear when Hindu educational system meant only with religious activities, but is actually a field study in line with the modern Hindu education starting from the beginning of the development of students up to high levels and goals of national education. The results of this research were Hindu educational system is not fully implemented in Indonesia but rather adapt to the existing formal education. So in their implementation was carried out in the form of informal education pasraman education developed between education system taking Hindu with a curriculum used follows the national education curriculum. This paper presents the essence of Hindu educational system with the national education system, both of which have a purpose that education must be the result of the knowledge, attitudes and skills. Therefore, the implementation of the synergies of the Hindu education with national education should be implemented to achieve a winning Indonesian people and competitive in all areas of life in the confront era of globalization.